Alain Badiou. - Feltham, Oliver (Live Theory., 2008)
Alain Badiou is undoubtedly the most exciting and influential voice in contemporary French philosophy and one of the most important theorists at work today. His impact on continental philosophy and the wider philosophy community, politics and the arts in the last twenty years has been immense. Alain Badiou: Live Theory offers a concise and accessible introduction to his work and thought, laying out the central themes of his major works, including his magnum opus, Being and Event, and its long-awaited sequel, Logics of Worlds . Oliver Feltham explores the fundamental questions through which B.